Financial management of health care organizations : an introduction to fundamental tools, concepts, and applications - Zelman, William N. (Finance professional collection, 2009)
Thoroughly revised, this third edition of Financial Management of Health Care Organizations offers an introduction to the most-used tools and techniques of health care financial management. Comprehensive in scope, the book covers a broad range of topics that include an overview of the health care system and evolving reimbursement methodologies; health care accounting and financial statements; managing cash, billings, and collections; the time value of money and analyzing and financing major capital investments; determining cost and using cost information in decision-making; budgeting and performance measurement; and pricing. In addition, this new edition includes information on new laws and regulations that affect health care financial reporting and performance, revenue cycle management expansion of health care services into new arenas, benchmarking, interest rate swaps, bond ratings, auditing, and internal control. This important resource also contains information on the 2007 Healthcare Audit Guide of the American Institute of Certified Public Accountants (AICPA).